Fair Value Analysis of Shares amidst Fintech Competition Pressure: A Case Study at PT Bank BNI - Muhammad Faisal AR Pelu; Syamsuri Rahim; Mildazani Mildazani; Muslim Muslim (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2020)
This study aims to determine the fair value of PT. Bank Negara Indonesia Tbk amid pressure from fintech competition. This research uses secondary data. Secondary data needed in this study are financial statements and stock price data of PT. Bank Negara Indonesia (BNI) Tbk, which was listed on the Indonesia Stock Exchange from 2014-2018. The data collection method used in this study is the documentation method. The data analysis method used in this research is quantitative descriptive. This study uses a Discount Cash Flow approach to calculate and determine the fair value of company shares. The results showed that: the cost of equity produces the desired rate of return of investors. Growth obtains a number that will be used to determine the FCFE projection. FCFE shows how efficient a company is in using cash. Terminal Value obtains the value used as the basis for calculating the current value. Discount factor decreases in value every year. Discounted FCFE generates an assumption of value growth every year. Price Value illustrates the assumption that the value obtained in the future is below the value spent. Equity value offers indicative value in terms of potential. Fair value produces value below market value. Bank BNI shares, in the overvalent category. Fintech, with its various innovations and sophistication, has made the role of banks slowly taken over.